Addressing the learning needs of at-risk students at a South African university - du Preez, Madge; McGhie, Venicia (South African Journal of Higher Education, 2016)
This paper reports on the findings of an action research, pilot project called One-by-One. Six first-year students in the extended curriculum programme at the University of the Western Cape were mentored, supported and closely monitored during 2011 to overcome their low morale and fear of failure. The paper draws on motivation theories, social theories of learning and student learning theories as theoretical framework. These theories assisted with the focus of the project which was on developing and strengthening the students personal and collective agency capabilities. Data was collected through a questionnaire, written reflective journal entries and discussions in one-on-one mentoring and group workshop sessions. The significance of the project lies in the fact that it provided the staff with practical steps on how to develop and strengthen the students perceived self-efficacy in the learning process.